The Influence of Leadership and Work Motivation on Employee Discipline at PT Bank XYZ in West Jakarta - Christina Sirait, Juwita; Poerwita Sary, Fetty (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
This research examines the influence of leadership and work motivation on employee discipline at PT Bank XYZ in West Jakarta. Bank XYZ, as one of the leading financial institutions in Indonesia, is committed to employee development and maintaining a positive work culture. The lack of employee discipline can affect operational efficiency and customer service. Therefore, leadership and work motivation are considered crucial factors in influencing the level of employee discipline. This study utilizes data from 2020 to 2022 to analyze the relationship between these variables. The analysis results indicate that both leadership and work motivation have a positive and significant impact on employee discipline. The better the leadership and work motivation, the higher the level of employee discipline. The implication is the importance of the leader's role in setting a good example and providing motivation to employees to achieve optimal performance. This research contributes to the development of human resource management theory, particularly in the context of the banking industry. Additionally, the findings can serve as a guide for companies to improve employee performance through the optimization of leadership and work motivation.